Clinical and Immunological Aspects of Newcastle Disease Vaccination in Budgerigars (Melopsittacus undulatus) - Denadai, Janine; Paulillo, Antonio Carlos; Schmidt , Elizabeth Moreira dos Santos; Martins, Gislaine Regina Vieira; Lapera, Ivan Moura; Carrasco, Adriano de Oliveira Torres (International Journal of Poultry Science, 2010)
Clinical and immunological aspects of budgerigars, vaccinated against Newcastle disease were evaluated. Seventy-two birds were distributed into four different experimental groups, vaccinated or not against Newcastle disease: GI (Ulster 2C strain), GII (B1 strain), GIII (LaSota strain) and GIV (not vaccinated-control). The immune response was evaluated by the HI test. Budgerigars showed high antibody titres when vaccinated against Newcastle disease with Ulster 2C, B1 and LaSota strains. No clinical signs associated with post-vaccinal reactions were observed.